Evaluasi Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pembelajaran Jarak Jauh di Kelas 5 SDIT AL-Haraki Depok - Nasiha Syaqina Laily; Dindin Ridwanudin (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
This study aims to determine the use of ICT in distance learning in grade 5 SDIT Al-Haraki Depok and evaluate the benefits of information and communication technology in distance learning in grade 5 SDIT Al-Haraki Depok. This research is an evaluative qualitative descriptive study with the aim of examining the use of information and communication technology in distance learning in grade 5 SDIT Al-Haraki Depok. The subjects in this study were school principals, 5th grade homeroom teachers, and 5th grade students for the 2020/2021 academic year. The results of this study indicate that the overall use of ICT in distance learning has been going well and can be maintained. However, there are several main obstacles, namely an unstable network, psychosocial conditions of parents, students and teachers who are already saturated with the distance learning process, and also the lack of variety in the use of learning applications, so that some students are still less enthusiastic in learning and this affects the learning process. student learning outcomes.